Equity in the Education of English Learners of Hmong Descent - Vang Yang, Xee (School of Education, University of Wisconsin-Stevens Point, 2020)
This qualitative case study of a Hmong bilingual El program operating using the dual-language-immersion model in Paradigm 2.0 examined education of English learners of Hmong descent. I observed and interviewed seven educators and one administrator during a summer term at one school using dual-language-immersion in Hmong for students of Hmong descent. Analyses sought to identify how theories of educational equity were instantiated in this bilingual program. Equity was defined in this study as equitable distribution of resources, being culturally relevant and responsive to the needs of students and integrating a curriculum that is inclusive of the whole child. Through analyses of data from interviews and observations, I found two main themes and eighteen sub-themes. I drew five conclusions and made ten recommendations. The administrator and educators in this study faced challenges in adapting their practices under policies in a paradigm that did not foster equity, and that systemic oppression must be tackled at its source in a manner that is cohesive and collaborative.
Keywords: equity; equitable access; Hmong; English learners; culturally relevant; culturally responsive; critical lens